Comparative pharmacokinetics and safety of lansoprazole oral capsules and orally disintegrating tablets in healthy subjects - Freston, J. W.; Chiu, Y.‐L.; Mulford, D. J.; Ballard II, E. D. (Alimentary pharmacology & therapeutics, 2003)
Summary Background : Many individuals with acid‐related gastrointestinal disorders have difficulty in swallowing oral agents. Aim : To compare the bio‐availability of a single dose of lansoprazole orally disintegrating tablet with that of an intact capsule. Methods : One hundred and twenty healthy subjects participated in two prospective, Phase I, open‐label, two‐period cross‐over studies to receive lansoprazole, 15 mg or 30 mg. Within each study, subjects were randomized into two parallel cohorts consisting of 30 subjects per regimen, dispensed in opposing sequence over two periods separated by a 7‐day washout period. Blood samples were collected on day 1 of both periods to determine the pharmacokinetic parameters. Results : Tmax occurred at 1.8 and 2.0 h with the 15‐mg and 30‐mg tablets, respectively. Dose proportional increases in Cmax, AUCt and AUC∞ were observed in the 15‐mg and 30‐mg groups. The terminal elimination half‐lives (t1/2) were identical in both dose groups (1.18 h). Lansoprazole administered as the orally disintegrating tablet was bio‐equivalent to the intact capsule formulation with respect to Cmax, AUCt and AUC∞. Conclusions : Lansoprazole orally disintegrating tablets, 15 mg and 30 mg, are bio‐equivalent to the respective dose administered as the intact capsule. This novel dosage formulation represents an option for patients who have difficulty in swallowing oral agents.